Les reprsentations des enfants de 5-6 ans sur la fusion et la solidification du sel, comme support pour le dploiement des activitis didactiques - Ravanis, Konstantinos (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
<span lang="EN-US" style="color: windowtext; font-family: 'Arial','sans-serif'; font-size: 9pt; font-weight: normal; mso-bidi-font-size: 10.0pt; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US;">The representation of the properties and phenomena of the physical world exists from the beginning of life, as a first datum of reality. In several studies focused on children's representations we find that these representations these representations are critical to education and are often incompatible with the scientific model. This article presents the results of an empirical research on the representations of young children for melting and solidification of salt. The research sample consisted of 79 pre-school children (five to six years old) from one state kindergarten in Greece. Data were collected through expanded, open type, semi-structured individual conversations between a child of the sample and one researcher. The results of the interviews show that these children use different types of representations, the majority dominated by the nature of the substance under study.